Carbon Dioxide Injection in Bamboo Cement Board Manufacturing - Bakri Bakri; Suhasman Suhasman (Jurnal Ilmu dan Teknologi Kayu Tropis, 2014)
The objective of this study was to evaluate the effect of CO2 injection in liquid phase to the physical and mechanical properties of cement board made from bamboo particles of Gigantochloa atter, Dendrocalamus asper and Schizostachyium brachycla. Mixtures of bamboo culm particles, cement, and water in the ratio by weight of 1:2.5:1.25 were casted in iron plate mold of (25x25x1) cm3, pressed and then hold for 24 h to obtain the target density of 1 g cm-3. The board was then injected by CO2 in liquid phase for 30 min of curing time period. Evaluation of physical and mechanical properties of board were evaluated in accordance to JIS A 5417-1992 standard. The results showed that moisture content of the boards was 3.15-3.62%, density was 0.68-0.80 g cm-3, water absorption and thickness swelling after immersed in cold water for 24 h were 45.11-57.60%, and 0.65-0.87%, respectively. The internal bond, modulus of elasticity and modulus of rupture were 0.18-0.74, 1339-5031, and 40.12-79.59 kg cm-2, respectively. Only cement board made from mixture of G. atter particles, cement and water met physical properties requirement of JIS A 5417-1992 standard. However, no cement board fulfilled the mechanical properties requirement of JIS A 5417-1992.Key words: bamboo, carbon dioxide injection, cement board